Relationship between rainfall and prevalence of the surveillance diseases during flood, Maha Sarakham province - Prathumchai, Nuchnapa; Thunyasirinon, Chuleewan; Khiewkhern, Santisith (Disease Control Journal, 2024)
Floods are the most frequent type of natural disasters, representing approximately 45% of the total number of reported disasters worldwide. This disaster, especially flooding, can cause damage to the economy, society, environment, and people. This study aimed to determine the relationship between rainfall and prevalence of the diseases under surveillance during floods. The rainfall data were obtained from Meteorological Department from 2009 to 2018 and number of patients were obtained from the hospitals in Maha Sarakham Province during the same period. Data were analyzed by descriptive statistics and One-Way ANOVA statistics at p-value<0.05. The results showed that hand, foot, and mouth disease, dengue hemorrhagic fever, diarrhea, and influenza are significantly associated with rainfall (p=0.000, 0.002, 0.031, and 0.028, respectively). These diseases are 4 of 7 listed notifiable diseases during floods by the Department of Disease Control. The findings can be used as information for prevention and preparedness of treatment and medical supplies of flood-related diseases. Additionally, meteorological data can also be employed to provide early warnings on potential incidents and to help ensure preparedness.